School-Based Nutrition Programs Are Associated with Reduced Child Food Insecurity over Time among Mexican-Origin Mother-Child Dyads In Texas Border Colonias(1)(2) - Nalty, Courtney C. (American Society for Nutrition, 2013)
In 2011, an estimated 50.2 million adults and children lived in US households with food insecurity, a condition associated with adverse health effects across the life span. Relying solely on parent proxy may underreport the true prevalence of child food insecurity. The present study sought to understand mothers’ and children’s (aged 6–11 y) perspectives and experiences of child food insecurity and its seasonal volatility, including the effects of school-based and summertime nutrition programs. Forty-eight Mexican-origin mother-child dyads completed standardized, Spanish-language food-security instruments during 2 in-home visits between July 2010 and March 2011. Multilevel longitudinal logistic regression measured change in food security while accounting for correlation in repeated measurements by using a nested structure. Cohen’s κ statistic assessed dyadic discordance in child food insecurity. School-based nutrition programs reduced the odds of child food insecurity by 74% [OR = 0.26 (P < 0.01)], showcasing the programs’ impact on the condition. Single head of household was associated with increased odds of child food insecurity [OR = 4.63 (P = 0.03)]. Fair dyadic agreement of child food insecurity was observed [κ = 0.21 (P = 0.02)]. Obtaining accurate prevalence rates and understanding differences of intrahousehold food insecurity necessitate measurement at multiple occasions throughout the year while considering children’s perceptions and experiences of food insecurity in addition to parental reports.